Outcomes of Living Kidney Donor Candidates and Living Kidney Recipient Candidates with JC Polyomavirus and BK Polyomavirus Viruria. (20th August 2021) - Querido, Sara; Ormonde, Carolina; Adragão, Teresa; Costa, Inês; Pessanha, Maria Ana; Gomes, Perpétua; Weigert, André
Abstract : Introduction . Recent data have emerged about a protective association between JCV viruria and chronic kidney disease (CKD). Material and Methods . Single-center retrospective cohort study; 230 living kidney donors (LKD) candidates and 59 potential living kidney receptors (LKR) were enrolled. Plasma and urinary JCV and BKV viral loads were measured in all LKD candidates and in nonanuric LKR candidates. Twenty-six living kidney transplant surgeries were performed. LKR were followed in order to evaluate BKV and JCV viremia and urinary viral shedding after KT. Results . In LKD candidates, JCV viruria was negatively associated with proteinuria of >200 mg/24 hours (JC viruric LKD: 12.5% vs JCV nonviruric LKD: 26.7%, p = 0.021, OR:0.393; 95% CI: 0.181–0.854). In a multivariate analysis, LKD candidates with JCV viruria had a lower risk of proteinuria of >200 mg/24 hours (p = 0.009, OR: 0.342, 95% CI: 0.153–0.764), in a model adjusted for age, gender, presence of hypertension, and eGFR <80 mL/min. Prevalence of JCV viruria was higher in LKD candidates when compared with LKR candidates (40.0% vs 1.7%, p < 0.001 ). Among the 26 LKR, 14 (53.8%) KT patients evolved with JCV viruria; 71.4% received a graft from a JCV viruric donor. Conclusion . Our data corroborate the recent findings of an eventual protective association between JCV viruria and kidney disease, and we extrapolated this concept to a South European population.